2005
DOI: 10.1111/j.1365-313x.2005.02597.x
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Solanum americanum genes encoding proteinase inhibitor II causes defective seed development

Abstract: SummaryProteinase inhibitor II proteins (PIN2) are serine proteinase inhibitors found in the Solanaceae. Here, we assign functions in seed development to two Solanum americanum genes, SaPIN2a and SaPIN2b, encoding proteinase inhibitor II. Their mRNAs and proteins have been previously localized to the reproductive tissues, including the inner cell layers of ovules in senescent flowers at the beginning of fruit development, suggestive of their endogenous roles in reproductive development. We have employed RNA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 54 publications
2
49
1
1
Order By: Relevance
“…Moreover, we could not observe any other PIdependent developmental phenotype that had been reported for other species. There was no significant difference in flower diameter (Sin et al, 2006), number of reproductive units (Zavala et al, 2004a), plant growth (Zavala et al, 2004a;Xie et al, 2007), or trichome morphology and density (Liu et al, 2006;Luo et al, 2009). As a consequence, we infer that the developmental importance of SPI2a and SPI2b differs between species.…”
Section: Spis Differ In Substrate Specificity But Play No Major Role mentioning
confidence: 78%
See 4 more Smart Citations
“…Moreover, we could not observe any other PIdependent developmental phenotype that had been reported for other species. There was no significant difference in flower diameter (Sin et al, 2006), number of reproductive units (Zavala et al, 2004a), plant growth (Zavala et al, 2004a;Xie et al, 2007), or trichome morphology and density (Liu et al, 2006;Luo et al, 2009). As a consequence, we infer that the developmental importance of SPI2a and SPI2b differs between species.…”
Section: Spis Differ In Substrate Specificity But Play No Major Role mentioning
confidence: 78%
“…Sin et al (2006) demonstrated that S. americanum silenced in the expression of PIN2a and PIN2b aborted around 80% of its seeds. Surprisingly, we found this effect to be very small in S. nigrum.…”
Section: Spis Differ In Substrate Specificity But Play No Major Role mentioning
confidence: 99%
See 3 more Smart Citations